2010
DOI: 10.1021/bi901867s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium-Sensitizing Mutations on Calcium Binding and Exchange with Troponin C in Increasingly Complex Biochemical Systems

Abstract: The calcium dependent interactions between troponin C (TnC) and other thin and thick filament proteins play a key role in regulation of cardiac muscle contraction. Five hydrophobic residues Phe 20 , Val 44 , Met 45 , Leu 48 and Met 81 in the regulatory domain of TnC were individually substituted with polar Gln, to examine the effect of these mutations that sensitized isolated TnC to calcium on: 1) calcium binding and exchange with TnC in increasingly complex biochemical systems and 2) calcium sensitivity of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
93
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(110 citation statements)
references
References 39 publications
10
93
0
Order By: Relevance
“…2ϩ Binding Studies-Our laboratory has developed a fluorescent troponin C, TnC IAANS T53C , which minimally affects cTnC function and reports the structural changes that occur in the regulatory domain of cTnC upon Ca 2ϩ binding and dissociation on the thin filament (17,32). This fluorescent TnC enabled the Ca 2ϩ binding studies reported here.…”
Section: Thin Filament Camentioning
confidence: 99%
See 3 more Smart Citations
“…2ϩ Binding Studies-Our laboratory has developed a fluorescent troponin C, TnC IAANS T53C , which minimally affects cTnC function and reports the structural changes that occur in the regulatory domain of cTnC upon Ca 2ϩ binding and dissociation on the thin filament (17,32). This fluorescent TnC enabled the Ca 2ϩ binding studies reported here.…”
Section: Thin Filament Camentioning
confidence: 99%
“…A Ca 2ϩ -sensitizing TnC will be required to correct the DCM thin filament behavior. By mutating the hydrophobic pocket of the regulatory domain of TnC, Ca 2ϩ -sensitizing TnC constructs can be engineered (32,33). For instance, the TnC M45Q mutation increased thin filament Ca 2ϩ sensitivity ϳ8-fold when compared with the control Tn IAANS T53C ( Fig.…”
Section: Thin Filament Camentioning
confidence: 99%
See 2 more Smart Citations
“…To slow CaM's N‐terminal rate of Ca dissociation, we stabilized its Ca binding induced open conformation by mutating a key hydrophobic residue, Met 37, into a polar residue Gln. Based on our previous studies on CaM's evolutionary relative troponin C, a similar mutation in troponin C facilitates the Ca‐induced structural transition of the protein, thus stabilizing Ca binding 42, 43. As shown in Figure 5A, mutating Met 37 to Gln (CaM M37Q) drastically slowed the rate of N‐terminal Ca dissociation from CaM.…”
Section: Resultsmentioning
confidence: 90%